Biomethane: A Renewable Resource as Vehicle Fuel - Federica Cucchiella; Idiano D'Adamo; Massimo Gastaldi (Resources, 2017)
The European Union (EU) has set a mandatory target for renewable fuels of 10% for each member state by 2020. Biomethane is a renewable energy representing an alternative to the use of fossil fuels in the transport sector. This resource is a solution to reach this target. Furthermore, it contributes to reducing carbon dioxide emissions, gives social benefits and increases the security supply. Sustainability is reached also when the economic opportunities are verified. This work studies the profitability of small plants of biomethane, which is sold as vehicle fuel using the Net Present Value (NPV) and Discounted Payback Time (DPBT). The paper shows in detail the method used for the economic assessment of two typologies of feedstock recovered: (i) municipal solid waste and (ii) agricultural waste. Detailed information about the various parameters that affect the profitability of biomethane is given, and several case studies are analyzed as a function of two variables: subsidies and selling price. The results support the commercialization of small-scale plants, reducing also several environmental issues. The role of subsidies is strategic, and the profitability is verified only in some case studies